Broad-spectrum antitumor analysis of the telomerase activity inhibitor TPCH derived from the human constitutively expressed protein LPTS/PinX1 - Zhou, Hongchang; Zhang, Xiaoying; Wang, Yao; Wu, Yongqiang; Wang, Ling; Hu, Chen; Zhang, Ting; Zhang, Hui; You, Dian; Zhao, Mengli; Zhao, Mujun; Li, Anqi; et al. (Frontiers in Oncology, 2025)
BackgroundThe human liver-related putative tumor suppressor LPTS/PinX1 is a gene encoding a telomerase inhibitory protein. Overexpression of LPTS/PinX1 protein can inhibit the growth of multiple telomerase-positive cancer cell lines. LPTS/PinX1 has therapeutic potential for cancer.MethodsWe statistically analyzed the level of LPTS/PinX1 protein in 9 cancer cell lines. LPTS/PinX1158-328 (exon 7 of LPTS) was fused with TAT to generate the recombinant protein TPCH. The effects of the TPCH protein on cell growth, senescence and apoptosis in 14 cell lines were analyzed in vitro and in vivo.ResultsThe purified TPCH protein was delivered into cells and inhibited telomerase activity. Also it inhibited the growth of 11 telomerase-positive cancer cell lines, was ineffective in 3 telomerase-negative cell lines in vitro and inhibited the growth of MCF-7, A549 and SW480 cell line-derived xenograft (CDX) and liver cancer patient-derived xenograft (PDX) mouse models in vivo. The inhibitory effect on the cancer cell growth was negatively correlated with the telomere length. The TPCH protein induced senescence and apoptosis in telomerase-positive cancer cells through the p21 signaling pathway and inhibited the migration of telomerase-positive cancer cells.ConclusionsThe TPCH protein strongly inhibited telomerase activity and suppressed the growth of all tested human telomerase-positive cancer cell lines in vitro and in vivo. Therefore, it could be developed as a broad-spectrum anticancer agent with low toxicity.